Risk eating behaviors, perception of parental practices and assertive behaviors in high school students - Bautista-Díaz, María Leticia (2020)
Background: Late adolescence is considered a risk stage for psychological health. The objective of this research was evaluating the association among risk eating behaviors (REB), parental practices and assertive behavior in high school students according to sex. Method: With a non-experimental design and transversal study participated 200 students (104 men and 96 women) from a public high school with age mean of 16.52 (SD = 1.05 years), who after signing informed consent fulfilled the Eating Attitudes Test-26 (EAT), the Scale of Parental Practices for Adolescents (PP-A) which has nine subscales, four towards the father (PPf) and five towards the mother (PPm) and the Assertive Behavior Scale (CABS), all of them validated for Mexican population. Results: Differential associations were found according to sex: in women, EAT-26-Total was associated with CABS-Total, parental Communication, maternal Imposition and maternal Psychological Control (rs = -.36, .25, -.28, -.36, respectively); but in men, was only associated with parental Imposition (rs = -.30).  The CABS-Total was associated with all PPm subscales in women (range rs = .22 to .36) and in men only with Communication, Psychological and Behavioral Control (rs = .30 .35, -.23). Conclusion: The high school students –women to a greater degree– higher REB greater aggressive style (no assertiveness), greater maternal psychological control and less maternal behavioral control.